91. Functional sub-structures of lower urinary tract in cervix cancer: Contouring and dose distribution. (December 2018) - Spampinato, S.; Fokdal, L.; Marinovskij, E.; Axelsen, S.; Pedersen, E.M.; Pötter, R.; Lindegaard, J.; Tanderup, K.
Abstract : Purpose: Radiotherapy related urinary morbidity includes various clinical endpoints (i.e. frequency, cystitis, incontinence, bleeding, fistula) that may be related to various anatomical sub-structures. Nowadays, reporting of bladder dose is based on the contouring of the outer bladder wall. This study aims to investigate contouring and dose evaluation of sub-structures potentially responsible for urinary morbidity after radiochemotherapy and Image Guided Adaptive Brachytherapy (IGABT) in locally advanced cervical cancer (LACC). Methods: The study hypothesis is that different bladder sub-structures (trigone, bladder neck, urethra) are related to different morbidity endpoints. Structures were contoured for all BT fractions extracting the DVH parameters: outer bladder wall ( D 2cm3, D 0.1cm3 ), ICRU Bladder point, trigone ( D 2cm3, D 0.1cm3 ), bladder neck ( D 0.1cm3 ), and urethra ( D 0.1cm3, D 2cm3 ) . Doses to the Posterior-Inferior Border of the Pubic Symphysis (PIBS) points were also extracted as urethral sphincters surrogate. Finally, the Vaginal Reference Length (VRL), defined as the PIBS point-source distance, was measured. A total of 110 LACC [FIGO Stage: IB(8), IIA(3), IIB(78), IIIA(2), IIIB(9), IVA(1), IVB(9)] patients according to the EMBRACE protocol was selected. Results: The reported values represent the cumulative EBRT+BT dose in EQD2. Median D 2cm3 values were 71.7[56.0–81.8] and 55.2[46.3–75.6] Gy for bladder wall and trigone, respectively. Bladder wall dose was systematically higher, and hotspots often placed outside the trigone. Median ICRU Bladder point dose was 63.6[48.4–90.7] Gy, Median D 0.1cm3 values for bladder wall, trigone, bladder neck and urethra were 82.0[68.2–109.8], 66.8[48.3–105.6], 59.5[46.5–88.3], and 50.4[44.8–88.3] Gy, respectively. Median PIBS and PIBS+2 cm point doses were 40.5[3.6–60.5] and 50.9[40–78.5] Gy, while median VRL was 5.9[1.9–8.2] cm. Conclusions: The study showed that the parameters currently used for IGABT bladder dose reporting ( D 2cm3, ICRU Bladder point) do not fully describe the dose distribution in the lower urinary. D 2cm3 for the outer bladder wall is often higher than trigone dose, while the ICRU bladder point better represents the trigone D 2cm3 and D 0.1cm3, as shown in Fig. 1. PIBS point does not seem good surrogates for urethral sphincters, whereas VRL is a good indicator for bladder base dose sparing. Further understanding of dose-effect relationships for the bladder may be gained by future systematic delineation of bladder sub-structures.